2022
DOI: 10.1097/wco.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

Update on genetics of amyotrophic lateral sclerosis

Abstract: Purpose of reviewALS genetics are highly dynamic and of great interest for the ALS research community. Each year, by using ever-growing datasets and cutting-edge methodology, an array of novel ALS-associated genes and downstream pathomechanisms are discovered. The increasing plenty and complexity of insights warrants regular summary by-reviews.Recent findingsMost recent disease gene discoveries constitute the candidate and risk genes SPTLC1, KANK1, CAV1, HTT, and WDR7, as well as seven novel risk loci. Cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 48 publications
0
34
0
2
Order By: Relevance
“…The familial forms of ALS have been linked to a myriad of distinct genes. Indeed, since the discovery in 1993 of the first causative gene, the one coding for Cu/Zn superoxide dismutase ( SOD1 ) (Rosen et al, 1993), more than 50 others associated with disease pathogenesis and susceptibility have been identified (Al-Chalabi et al, 2017; Brenner and Weishaupt, 2019), and research continues to uncover at an incredibly rapid pace novel monogenic disease genes, genetic risk factors, as well as disease-modifying genes. Due to the extremely heterogeneous and complex genetic architecture of ALS, the distinction between fALS and sALS is often blurred, the etiology of the disease not yet clearly defined for most patients and, as a consequence, effective treatments remain elusive (Morello et al, 2020).…”
Section: Introduction: Amyotrophic Lateral Sclerosis and Vapbmentioning
confidence: 99%
“…The familial forms of ALS have been linked to a myriad of distinct genes. Indeed, since the discovery in 1993 of the first causative gene, the one coding for Cu/Zn superoxide dismutase ( SOD1 ) (Rosen et al, 1993), more than 50 others associated with disease pathogenesis and susceptibility have been identified (Al-Chalabi et al, 2017; Brenner and Weishaupt, 2019), and research continues to uncover at an incredibly rapid pace novel monogenic disease genes, genetic risk factors, as well as disease-modifying genes. Due to the extremely heterogeneous and complex genetic architecture of ALS, the distinction between fALS and sALS is often blurred, the etiology of the disease not yet clearly defined for most patients and, as a consequence, effective treatments remain elusive (Morello et al, 2020).…”
Section: Introduction: Amyotrophic Lateral Sclerosis and Vapbmentioning
confidence: 99%
“…At the end of the study period, all recruiting hospitals were asked to report the number of available ALS patients during the recruitment period, the number of patients who were offered participation but declined, and the number of patients who were not offered participation. [18], UniProtKB [48] and recent published literature [1,6,[19][20][21]. AD, autosomal dominant; ALS, amyotrophic lateral sclerosis; AR, autosomal recessive; FTD, frontotemporal dementia; HSAN, hereditary sensory and autonomic neuropathy; HSP, hereditary spastic paraplegia; NA, not available; PLS, primary lateral sclerosis; SCA, spinocerebellar ataxia; SMA, spinal muscular atrophy; XLD, X-linked dominant.…”
Section: Study Populationmentioning
confidence: 99%
“…During bioinformatic filtering, 30 genes relevant to ALS were included and analyzed (Table 1). The selected genes were chosen based on information from OMIM [18] and recently published literature [1,6,[19][20][21]. The identified variants were filtered based on dominant and recessive inheritance models, using gnomAD (https://gnomad.broadinstitute.org/) minor allele frequencies of 0.1% and 2.0%, respectively.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…The field of genetic ALS continues to develop rapidly with multiple disease gene discoveries per year (128), with the autosomal dominant inheritance of a hexanucleotide expansion in the first intron of the C9orf72 gene being the most common cause of familial ALS in people of Northern European ancestry, also as a major contributor to frontotemporal pathology in ALS. DTI studies in patients with C9orf72 expansion in crosssectional and longitudinal design demonstrated alterations in motor tracts (129)(130)(131); in addition, further white matter areas were found to be affected, e.g., in the frontal white matter (132) and segmentally in the corpus callosum (133).…”
Section: Mr Findings With Respect To Genetic Phenotypementioning
confidence: 99%